PSYCHOLOGICAL AND PEDAGOGICAL FEATURES OF THE USE OF GAME METHODS OF TEACHING ENGLISH (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article explores the psychological and pedagogical aspects of using game-based methods for teaching English as a second language. It provides an in-depth analysis of the literature related to game-based teaching, outlines various methods and approaches, discusses the results and their implications, and concludes with recommendations for educators looking to integrate games into their language teaching curriculum.